Modeling Thin Layer Drying of Amaranth Seeds under Open Sun and Natural Convection Solar Tent Dryer - Ronoh, E.K.; Kanali, C.L.; Mailutha, J.T.; Shitanda, Douglas (My University, 2009)
Thin layer drying studies of amaranth (Amaranthus cruentus) seeds were carried out under open sun and natural convection solar tent dryer. The ambient temperature and relative humidity ranged from 22.6–30.4 °C and 25–52 %, respectively, while the inside temperature and relative humidity in the solar dryer ranged from 31.2–54.7 °C and 22–34 %, respectively. Fresh amaranth seeds with the average moisture content of 64 % (dry basis) were dried under both conditions for seven hours to the final moisture content of about 10 % (dry basis). A non-linear regression analysis was used to develop drying models for amaranth seeds. The models were compared using the coefficient of determination (R2), root mean square error (RMSE) and the reduced chi-square (E2) in order to determine the one that best represented thin layer drying characteristics of amaranth seeds. The results show that the Page model satisfactorily described the drying of amaranth seeds with R2of 0.9980, E2of 0.00016 and RMSE of 0.01175 for bottom layer and R2of 0.9996, E2of 0.00003 and RMSE of 0.00550 for top layer of the drying rack. Similarly, the Page model attained R2of 0.9965, E2of 0.00027 and RMSE of 0.01540 for the open sun. This shows that there was a good agreement between the predicted and actual moisture changes in drying of amaranth seeds under both conditions.
Keywords: Thin layer; Open sun; Solar tent dryer; Amaranth; Drying models; Natural convection